Pulsed thermal treatment of carbon up to 3000 °C using an atomic absorption spectrometer - Putman, Kate; Sofianos, M.; Rowles, Matthew; Harris, P.; Buckley, C.; Marks, Nigel; Suarez-Martinez, Irene (Pergamon, 2018)
An atomic absorption spectrometer unit fitted with a graphite furnace module is used to perform high temperature treatment on three carbonized polymers: polyvinyl chloride (PVC), polyvinylidene chloride (PVDC) and polyacrylonitrile (PAN). Using short pulses up to 45 s, we heat small samples to a maximum of 3000 °C. High-resolution transmission electron microscopy and X-ray diffractometry are used to track the growth of crystallites in the materials as a function of the heating temperature. We observe the well-known behaviour of large crystalline graphite growth in PVC-derived samples and the formation of curved graphitic layers in PVDC- and PAN-derived samples. This graphite furnace atomic absorption spectrometer approach is an attractive alternative to conventional laboratory-scale graphite furnaces in research of high temperature treatment of carbon and other refractory materials.